Pengabdian Terhadap Masyarakat: Pelatihan Coding dalam Pendekatan Deep Learning : Penelitian - Zulfadewina Zulfadewina; Siti Ithriyah; Septi Fitri Meilana; Mimin Ninawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The development of digital technology requires elementary school teachers to have strong digital literacy, including the ability to integrate coding into learning. However, a needs analysis showed that teachers at SDN Batu Ampar 02 still struggled to understand basic coding concepts and were unable to apply them in their learning as required by the Independent Curriculum. Teachers' Scratch and Deep Learning skills will be improved by this Community Partnership Program (PKM). Lessons, demonstrations, hands-on practice, and mentoring were used. Teachers' comprehension improved significantly, marked by the ability to create simple coding projects and develop meaningful deep learning-based learning activities. This program successfully built teachers' readiness to integrate digital technology as a 21st-century learning medium